LEGAL POSITION OF BAWASLU'S RECOMMENDATION LETTER IN REGIONAL HEAD NOMINATION (CASE STUDY OF REGIONAL ELECTION AT THE GENERAL ELECTION COMMISSION OF MANDAILING NATAL REGENCY) - Artamilano, Yudha; Zulkarnaen, Zulkarnaen (Program Pascasarjana UIN Sumatera Utara, 2025)
This research analyzes the legal standing of Bawaslu's Recommendation Letter in regional head candidacy, using a case study of the Mandailing Natal Regency Election. The study examines the document's legal validity as an administrative requirement and its implications for democratic election principles. Employing normative juridical methods through analysis of legislation and relevant court decisions, findings indicate that Bawaslu's recommendation serves as a candidate integrity verification tool. However, its implementation at the Mandailing Natal KPU has sparked controversy due to varying interpretations of candidacy requirements. The study recommends regulatory improvements to prevent excessive discretion by regional KPU/Bawaslu.